Penggunaan Metode Analisis Risiko Dalam Proses Optimasi Profit Untuk Mengelola Ketidakpastian Bisnis - Pristiwanto Bani; Soegeng Wahyoedi; Melitina Tecoalu (Syntax Idea)
Business uncertainty is something that cannot be avoided in the business world. This uncertainty can be caused by various factors, such as economic, political, technological and social changes. Business uncertainty can cause profit fluctuations and can even result in losses for the company. The aim of this research is to explore the use of risk analysis methods in the profit optimization process to manage business uncertainty. This research uses a qualitative approach. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that the use of risk analysis methods in the profit optimization process can help companies identify, evaluate and manage business uncertainty more effectively. Risk analysis methods allow companies to better understand potential risks that can affect profitability, as well as design strategies to reduce or manage these risks.